Analysis of production planning activities in remanufacturing system - Magdalene, Andrew Munot; Abdullah, Hj. Yassin; Syed Tarmizi, Syed Shazali; Marini, Sawawi; Shirley, Jonathan Tanjong; Nur Tahirah, Razali (UMP Publisher, 2018)
This article examines the problem of uncertain quantities and quality conditions of used-products obtained from the customer-stream, third-party-stream & mixed-stream on remanufacturing cycle-time under three different remanufacturing resources policies. Simulation technique is used to model a remanufacturing system with uncertain quantities and quality conditions of used-products obtained from the customer-stream, third-party-stream and mixed-stream under three different remanufacturing resource policies. Findings show that the quantities of used-products either from the customer-stream or third-party-stream affect the remanufacturing cycle-time. For used-products form the mixed-stream, the percentage of used-products from the customer-stream greatly affects the remanufacturing cycle-time. The different remanufacturing resource policies also affect the remanufacturing cycle-time. It can be established and concluded that the performance of a remanufacturing system is affected by the uncertain quantities and quality conditions of used-products.